The state of the environment - Hinnawi, Essam E. (Butterworths, 1987)
The State of the Environment is the annual report of the United Nations that contains the current state of the environment and the biosphere as well as certain important environmental issues. The monograph also discusses social and economic issues and their implication to the environment. The book covers environmental concerns - air and atmospheric issues such as indoor air pollution, changes in atmospheric ozone, and the effects of carbon dioxide and other trace gases in the atmosphere; issues related to land and water such as land and soil loss, water quality, and food production; and power-